Implementation of Conversation Instruction to Upgrade Speech Skill (A Comparative Study between Pondok Pesantren Walisongo Sragen and Pondok Pesantren Darul Mukhlisin Temulus Ngawi)/تنفيذ تعليم المحادثة لترقية مهارة الكلام (دراسة مقارنة بين معهد والي سوعو سراغين و معهد دار المخلصين تيمولوس عاوي) - Susilaningtyas, Rohmah (UIN Raden Mas Said Surakarta, 2020)
This research aims to know: (1) explaining the history of Muhadasah program in boarding school Walisongo Sragen to increase Maharoh kalam in the year 2018/2019 (2) explaining the use of Muhadasah program in Walisongo Boarding School Sragen to increase Maharoh kalam in the year 2018/2019. This research uses qualitative research. The methods of collecting data are observations, interviews, and documentation. The test validity of data by using source triangulation. The analysis of data starts with data collection, data reduction, data presentation, and conclusion. The results showed that: 1) The Muhadasah Program is used to increase the Maharoh kalam this appears on the indicator of the student's achievement in the Maharoh Kalam, the program begins from the Salaf boarding school that only teaches the kitab kuning then Develop a muhadasah program to enhance the Maharoh kalam. The level of learning of the nature of the boarding school Walisongo Sragen starts from the basic level and intermediate and the upper level. (2) The activities of the muhadasah program were carried out every Sunday then implemented the use of Arabic in daily conversation although the implementation of this program is a new program for the Salaf boarding school. Although, the model of learning Muhadasah in the Waisongo boarding school Sragen by using memorization model, free muhadasah model, and the model of the answer (dialogue). Although, the method of evaluation is used with the observation approach and location approach.